Investigation of the viticultural and oenological situation of the Danube wine region in the hungarian grape and wine sector - Járdány, Krisztián (Studia Mundi – Economica, 2021)
The examination of the situation of wine regions in the Hungarian grape and wine sector cannot be without the traditional economic, technical, infrastructural, natural, cultural and social aspects, as well as the vine-wine-specific analyzes. The aim of the study is to shed light on the position of the Danube wine region in the Hungarian viticulture and wine sector, and on this basis to determine the development priorities of the wine region.To achieve my goals, I chose to process the relevant professional statistics. I processed the data using different mathematical methods.The statistical data were analyzed on a territorial basis and mainly on a time series basis.I focused on the trend-like analysis of the variables related to the production area data, grape yields and wine yields, as well as the wineries of the examined territorial unit.During the evaluation of the results, it was established that the viticulture and winemaking of the Danube wine region follow a completely different development curve compared to the other wine regions of Hungary. In the Danube wine region, there are large-scale wineries above the national average, and the revealed processes tend to favor the spread of these wineries.